Self-Understanding and the Care for Being: Heidegger's Ethical Thought - McNicolls, Christopher F. (My University, 1998)
Martin Heidegger is widely viewed as one of the most important philosophers of the 20th century. He is also generally viewed as an irrational metaphysician, as someone who has much to say about Being, but very little of it as making sense. Moreover, his thought is viewed as having very little to say about ethics; that is, the question of how we ought to live. In this thesis I argue that Heidegger's concept of Being is not irrational, and that his thought is primarily ethical. I argue that Heidegger's thought centres around the concept of authentic self -understanding, and that this form of selfunderstanding is deeply linked to solidarity with others and concern for things, what he describes as the care for Being
Keywords: philosophy; self-understanding; heidegger; ethics; thoughts; Ethics and Political Philosophy; Philosophy; Ethics and Political Philosophy